Introducing Javanese Culture Through Selected Texts in EFL Class - Kaukabilla Alya Parangu (JETLe (Journal of English Language Teaching and Learning), 2020)
The paper presents an overview of the research on teaching Javanese culture and describes the association between Javanese culture and English language teaching (ELT) through selected texts. A decisive question occurs in terms of ELT, whether to teach culture along with English. The implementation of selected text is one of the effective ways to encourage students to more appreciate and feel affection for their own culture. Since the native Javanese people obligates to be aware of their own culture. Using Javanese culture text means that the texts learned by the students are part of the Javanese original culture. Dealing with the text, the students will have a handle on the culture profoundly.  To answer such an incomprehensible question, this article shows the relation about the connection among literature and studies. This research also discusses a theoretical frame based on the experts’ insights and opinions. To summarize, this research displays various viewpoints in relation to this topic, offers different practical studies, and reaches some valuable conclusions.